Chromosome analysis of two species of sugar cane pests of the genus Mahanarva (Homoptera, Cercopidae) - Marin-Morales, Maria Aparecida [UNESP]; Zefa, Edison; Bertagna, Maína [UNESP]; Mathias, Maria Izabel Camargo [UNESP]; Arrigoni, Enrico (Firenze University Press, 2002)
Studies on the cytogenetics of Homoptera are scarce. Some references in the literature have reported a chromosome number for the genus ranging from n=5 to 19 and 2n=10 to 2n=39 chromosomes. The genus Mahanarva includes two species of agricultural importance as pests of sugar cane culture in Brazil. We report here the first data concerning the chromosome number and morphology of the species Mahanarva fimbriolata and M. posticata. The chromosome number observed for the two species was 2n=19 for males and 2n=20 for females. The sex determining mechanism of these species was of the XX/X0 type (for males and females, respectively), with chromosome X being the smallest in the complement.
Keywords: Cytogenetics Holocentric chromosome; Homoptera; Mahanarva; Sugar cane pest